A Compliant Force Control Scheme for Industrial Robot Interactive Operation - Xue, Xianfa; Huang, Haohui; Zuo, Lei; Wang, Ning (Frontiers in Neurorobotics, 2022)
To meet the enormous demand for smart manufacturing, industrial robots are playing an increasingly important role. For industrial operations such as grinding 3C products, numerous demands are placed on the compliant interaction ability of industrial robots to interact in a compliant manner. In this paper, an adaptive compliant control framework for robot interaction is proposed. The reference trajectory is obtained by single point demonstration and DMP generalization. The adaptive feedforward and impedance force controller is derived in terms of position errors, and they are input into an admittance controller to obtain the updated amount of position deviation. The compliant interaction effect is achieved, which is shown that the grinding head fits on the mouse curved surface and the interaction force is within a certain expected range in the grinding experiment based on the Elite robot. A comparative experiment was conducted to demonstrate the effectiveness of the proposed framework in a more intuitive way.